Studi Dan Analisa Campuran Tanah Lempung Dan Abu Sekam Padi Terhadap Nilai Permeabilitas Dengan Alat Falling Head - Setiawan, Dedi; Afriani, Lusmeilia; Setyanto, Setyanto (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
Soil permeability value for every construction is different. Such differences affect the strength of acivil construction to be built. Therefore it is necessary to attempt to manipulate the soilpermeability value by adding the additive to a soil permeability values obtained in order to meetthe standard of civil construction to be built. Among the many additives are used as soilstabilization materials, one of them is rice husk ash. Some recent researches in the field of CivilEngineering showed that rice husk ash mixture useful as a particularly clay soil stabilization.Because rice husk ash can fill the cavities that exist between the grains of ground.Soil samples tested in this study is clay derived from Perumahan Bhayangkara, KelurahanBeringin Jaya, Kecamatan Kemiling, Bandar Lampung. Rice husk ash used were obtained fromDusun Dantar, Kecamatan Padang Cermin, Kabupaten Pesawaran. This study was conducted todetermine the effect of rice husk ash to the soil permeability values.The results of analysis and calculations performed in the laboratory obtained averagepermeability value (k) for soil with 5% rice husk ash added, 10% rice husk ash added, and 15%rice husk ash added. The permeability value used to be compared with native soil (clay).Key words: clay, rice husk ash, permeability.